PENGEMBANGAN SISTEM INFORMASI ADMINISTRASI KARYAWAN BERBASIS MOBILE MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT - Lisa Lisa; Susanti Susanti; Zulpa Salsabila; Joosten Joosten (Jurnal Sistem Informasi, 2026)
PT Yorgo Anugerah Nusantara is a palm oil company with 510 employees whose leave, permit, overtime, and business-trip requests are handled entirely through paper forms. Each submission requires a physical handover from the employee to the Head of Department for approval, then to HRD for recording, resulting in delays of more than one working day per cycle and errors in documentation. This study develops a mobile-based employee request administration system that digitises those four workflows. The system is built using the Rapid Application Development (RAD) methodology, implemented with the .NET MAUI cross-platform framework, ASP.NET Core Web API, and PostgreSQL. System modelling used Use Case Diagrams and Activity Diagrams to capture both the current and proposed processes, and an Entity Relationship Diagram for data structure design. Functional validation applied Black Box Testing with the Equivalence Class Partitioning technique, all of which returned valid results. The system successfully replaces paper-based workflows with a digital end-to-end approval chain, enables real-time tracking of request status, and enforces automatic validation rules including a two-hour cap on permit duration, time-logic checks for overtime, and mandatory document attachment for sick leave.